Первый день: роман / Марк Леви ; [пер. с фр. Е. Тарусиной] - Леви Марк (Иностранка, 2012)
Экземпляры: аб. (2012) / Инвентарный номер: 54147 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Л 36 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44